Alpine Skiing With total knee ArthroPlasty (ASWAP): symmetric loading during skiing. (August 2015) - Pötzelsberger, B.; Stöggl, T.; Scheiber, P.; Lindinger, S. J.; Seifert, J.; Fink, C.; Müller, E.
Abstract : The aim of this pilot study was to determine the pressure distribution, symmetry of load between operated (OP) and non‐operated (NOP) leg, and pain level during alpine skiing in participants with unilateral total knee arthroplasty (TKA). The responses of the dependent variables were analyzed following a 10‐week guided skiing intervention of 2–3 days of skiing per week. Ground reaction force (GRF) was recorded bilaterally and was determined for 13 participants with TKA (65 ± 4 years) at pre‐ and post‐test. Additionally, pain perception was determined using a numeric rating scale in the OP leg at both test sessions and after each skiing day. No statistical differences were observed between OP and NOP legs for peak and average GRF as well as the asymmetry indices at pre‐test. Pain perception was low and was not increased as a consequence of the skiing intervention. In conclusion, alpine skiing did not lead to increased or decreased loading of the OP leg compared with the NOP leg. Therefore, alpine skiing may be allowed for patients with skiing experience and a good clinical outcome.